Review study on antibacterial activity of cherry leaf (Muntingia calabura) against Staphylococcus spp. and Salmonella spp. the most causing disease in livestock - Galuh Dianita Fitri; Heli Tistiana; Lilik Eka Radiati (Faculty of Animal Science, Universitas Brawijaya, 2017)
This research was conducted to know about the potential activity of cherry leaf (Muntingia calabura) as an alternative for disease caused by bacteria Staphylococcus spp. and Salmonella spp. The material of this review study was using some literature which related with papers topic. The method was using descriptive to explained and described in discussion chapter. Study of the effectiveness of cherry leaf (Muntingia calabura) had been compared with other natural antibacterial sources such as sirih leaf (Piper betle L.) and beluntas leaf (Pluchea indica L.). The result of this study showed cherry leaf was an effective natural antibacterial source because it has the widest inhibited zone against Staphylococcus spp. and Salmonella spp. which amount (19 mm and 37.7 mm) if compared with beluntas leaf (9.5 mm and 15.9 mm) and sirih leaf (16 mm and 17 mm). Another result, Muntingia calabura was effective for duck egg hatchability which amounts 87.74%, this result was high than chemical antibacterial (80.81%), beluntas leaf (44.05%) and sirih leaf (46.43%). From all literature about widest inhibited zone of natural antibacterial activity such as cherry leaf, beluntas leaf and sirih leaf against Salmonella spp. and Staphylococcus sp has the same extraction treatment. Moreover, the result from literature with explained about duck egg hatchery experiment between chemical antibacterial and natural antibacterial has the same treatment and duck egg incubation time. It was suggested to do further study to find out cherry leaf could be used as an alternative natural antibacterial for diseases caused by other bacteria.